Technical writing - Vicente, Corazon C.; Soria, Wenceslawa B.; Mogol, Ernani S. (Manila Technology Supply, 1976)
"Technical Writing is indeed designed to provide one aspect of the technical students' training -- the preparation of technical reports, letters, and articles, from the planning stage to the transmittal, mailing, or publication of the completed material... This book consists of reprints, excerpts, adaptations, abstracts, or summaries of discussions from various technical books and periodicals as well as original material."--Preface.
Preface -- Acknowledgement -- Chapter 1. Introduction -- Chapter 2. Basic techniques of technical writing --Chapter 3. The business letter -- Chapter 4. Technical reports -- Chapter 5. Technical magazine articles -- Appendixes.
Keywords: Technical writing; English language -- Technical English